Tingkat Keberhasilan Pelaksanaan Eliminasi Buatan Pada Ternak Sapi Di Kecamatan IV Angkat Candung Kabupaten Agam - Tinda Afriani (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
A field survey has been conducted to study the parameter achievements of artificial insemination (AI) by 4 different breeds of cows in IV Angkat Candung sub district of Agam District, West Sumatra. Data collected included conception rate (CR), service per conception (S/C) and calving rate from 496 cows which were divided into 4 offspring breeds: Simmental, Ongol, Charolais and Brahman. Results showed that the achievements of AI in the surveyed area were relatively high. The CR, S/C and Calving rate were found 76.68 %, 1.30 and 72.57 %, respectively. The most fertile cow was indicated by Ongol.